1973
DOI: 10.1083/jcb.59.2.491
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis and Turnover of Rat Liver Peroxisomes

Abstract: Early events in the biosynthesis of liver catalase were studied on female rats receiving intermediates, the first lacking heme and representing about 1 .6% of the total catalase content or 13 µg/g liver, the second containing heme and representing about 0 .5 1, 10 of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
2
1

Year Published

1973
1973
1996
1996

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(29 citation statements)
references
References 17 publications
1
25
2
1
Order By: Relevance
“…Thus, de Duve and Lazarow (15,16) showed that in whole-liver pulse chase experiments, catalase monomers associated with peroxisomes in vivo before being converted to tetramers. Similarly, Goodman et al (11) demonstrated that the kinetics of oligomerization and peroxisomal import of alcohol oxidase, an octameric flavoprotein from Candida boidinii, were similar, a finding that was interpreted as indicating that monomers are translocated into peroxisomes, where they then octamerize.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, de Duve and Lazarow (15,16) showed that in whole-liver pulse chase experiments, catalase monomers associated with peroxisomes in vivo before being converted to tetramers. Similarly, Goodman et al (11) demonstrated that the kinetics of oligomerization and peroxisomal import of alcohol oxidase, an octameric flavoprotein from Candida boidinii, were similar, a finding that was interpreted as indicating that monomers are translocated into peroxisomes, where they then octamerize.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above mentioned membrane proteins, ferritin (25), and catalase (26,27), some microsomai components, such as NADPH-cytochrome c reductase (28) and cytochrome P-450 (29), are believed to be synthesized at least partially on free ribosomes. The ribosomes themselves rapidly exchange their proteins with equivalent proteins in the cytoplasm (30).…”
Section: Discussionmentioning
confidence: 99%
“…pages 507-524 scribed in the preceding paper (22) . The animals were sacrificed at various times thereafter and their livers rapidly removed and chilled .…”
Section: Experimental Designmentioning
confidence: 99%
“…The PNS was fractionated as described below, and the fractions, as well as the original PNS, were assayed for protein, RNA, marker enzymes, TCA-precipitable radioactivity, and immunoprecipitable radioactivity. Immunoprecipitation was carried out exactly as described in the preceding paper (22), both on the whole fractions to yield whole fraction immunoprecipitates (WFI), and after partial purification of catalase to yield purified catalase immunoprecipitates (PCI) . Only goat globulins were used .…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation